In situ net primary productivity and photosynthesis of Antarctic sea ice algal, phytoplankton and benthic algal communities - McMinn, A; Pankowskii, A; Ashworth, C; Bhagooli, R; Ralph, P; Ryan, K (2010)
Primary production at Antarctic coastal sites is contributed from sea ice algae, phytoplankton and benthic algae. Oxygen microelectrodes were used to estimate sea ice and benthic primary production at several sites around Casey, a coastal area in eastern Antarctica. Maximum oxygen export from sea ice was 0. 95 mmol O2 m-2 h-1 (~11. 7 mg C m-2 h-1) while from the sediment it was 6. 08 mmol O2 m-2 h-1 (~70. 8 mg C m-2 h-1). When the ice was present O2 export from the benthos was either low or negative. Sea ice algae assimilation rates were up to 3. 77 mg C (mg Chl-a)-1 h-1 while those from the benthos were up to 1. 53 mg C (mg Chl-a)-1 h-1. The contribution of the major components of primary productivity was assessed using fluorometric techniques. When the ice was present approximately 55-65% of total daily primary production occurred in the sea ice with the remainder unequally partitioned between the sediment and the water column. When the ice was absent, the benthos contributed nearly 90% of the primary production. © 2010 Springer-Verlag.